The Global Lincoln: European Dimensions - Richard Carwardine; Jay Sexton (American Studies Journal, 2016)
Abraham Lincoln yearned to leave a permanent legacy. It is doubtful, however, that Lincoln, even when Confederates surrendered, appreciated just how far he had stirred hearts and minds at home and abroad. Yet his death, just days after Lee laid down his arms at Appomattox, prompted a quite extraordinary explosion of mourning around the world.